2020
DOI: 10.3390/agronomy10020269
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Removal Affects Maize Morphology and Grain Yield

Abstract: Increasing planting density is an important practice associated with increases in maize yield, but densely planted maize can suffer from poor light conditions. In our two-year field experiments, two morphologically different cultivars, ZD958 (less compact) and DH618 (more compact), were planted at 120,000 plants ha−1 and 135,000 plants ha−1, respectively. We established different leaf area index (LAI) treatments by removing leaves three days after silking: (1) control, no leaves removed (D0); (2) the two upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
(74 reference statements)
2
28
0
Order By: Relevance
“…Increasing plant density is an important way to improve maize grain yield, as was verified in our previous study 7 , 29 , 30 . In the present study, the grain yields were universally more than 11.0 Mg ha −1 (Table S1 ), and the highest obtained yield was 23.9 Mg ha −1 , which was obtained at a density of 10.5 plants m −2 (data not shown, Experiment II).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Increasing plant density is an important way to improve maize grain yield, as was verified in our previous study 7 , 29 , 30 . In the present study, the grain yields were universally more than 11.0 Mg ha −1 (Table S1 ), and the highest obtained yield was 23.9 Mg ha −1 , which was obtained at a density of 10.5 plants m −2 (data not shown, Experiment II).…”
Section: Discussionsupporting
confidence: 63%
“…In the present study, it was found that the leaf angle above the ear was positively correlated with marginal superiority (Table 1 , Fig. 1 C), which indicated that compact cultivars had more reasonable light distribution and thus weak competitiveness and weak marginal superiority 12 , 23 , 28 , which might have contributed to their high grain yields 30 .…”
Section: Discussionmentioning
confidence: 49%
“…The length (L) and maximum leaf width (Wmax) of each live leaf was measured, and the leaf area was calculated according to the formula of leaf area = L × Wmax × 0.75 [42,43]. The total leaf area per plant at silking maturity was defined as the maximum leaf area, which was measured for five plants per plot at the silking stage; the maximum leaf area index (LAImax) was calculated as follows: LAImax = total leaf area per plant × N/S, where N is the number of plants within a unit area of ground and S is the unit area of ground [41,43]. After physiological maturity, all plants in the central four rows of each plot, representing an area of 13 m 2 , were harvested manually to measure the grain yield.…”
Section: Sampling and Measurementsmentioning
confidence: 99%
“…The plants were separated into the stem, leaf, sheath, tassel, bract, kernel, and cob fractions and dried at 85 • C to a constant weight. The length (L) and maximum leaf width (Wmax) of each live leaf was measured, and the leaf area was calculated according to the formula of leaf area = L × Wmax × 0.75 [42,43]. The total leaf area per plant at silking maturity was defined as the maximum leaf area, which was measured for five plants per plot at the silking stage; the maximum leaf area index (LAImax) was calculated as follows: LAImax = total leaf area per plant × N/S, where N is the number of plants within a unit area of ground and S is the unit area of ground [41,43].…”
Section: Sampling and Measurementsmentioning
confidence: 99%
“…The number, stage and position of leaves removed may determine the degree of influence on maize performance. Raza et al (2019a) and Liu et al (2020) reported yield improvement in maize by removing two uppermost leaves around silking due to enhanced light distribution to the more competent leaves. However, a severe leaf removal (50%) at 25 and 35 days after silking (Shekoofa et al, 2012) and four and six top leaves at silking (Raza et al, 2019a) caused a significant yield loss in maize.…”
Section: Discussionmentioning
confidence: 99%